Effects of Bisphosphonate Therapy on Bone Mineral Density in Boys with Duchenne Muscular Dystrophy. (December 2020) - Ronsley, Rebecca; Islam, Nazrul; Kang, Mehima; Nadel, Helen; Reilly, Christopher; Metzger, Daniel; Selby, Kathryn; Panagiotopoulos, Constadina
The objective of this study was to estimate the comparative effectiveness of bisphosphonate therapy on bone mineral density (BMD) in patients with corticosteroid-treated Duchenne muscular dystrophy (DMD). A retrospective, comparative effectiveness study evaluating changes in BMD and fragility fractures in patients with DMD presenting to British Columbia Children's Hospital from 1989 to 2017 was conducted. Marginal structural generalized estimating equation models weighted by stabilized inverse-probability of treatment weights were used to estimate the comparative effectiveness of therapy on BMD. Of those treated with bisphosphonates (N = 38), 7 (18.4%), 17 (44.7%), and 14 (36.8%) cases were treated with pamidronate, zoledronic acid, or a combination of both, respectively, while 36 cases of DMD were untreated. Mean age of bisphosphonate initiation was 9.2 (SD 2.7) years. Mean fragility fractures declined from 3.5 to 1.0 following bisphosphonate therapy. Compared to the treated group, the untreated group had an additional 0.63-SD decrease (95% confidence interval [CI]: −1.18, −0.08, P = .026) in total BMD and an additional 1.04-SD decrease (95% CI: −1.74, −0.34; P = .004) in the left hip BMD, but the change in lumbar spine BMD (0.15, 95% CI: −0.36, 0.66; P = .57) was not significant. Bisphosphonate therapy may slow the decline in BMD in boys with corticosteroid-treated DMD compared to untreated counterparts. Total number of fragility fractures decreased following bisphosphonate therapy.